2018
DOI: 10.1177/1077558718778081
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Adjustments to Nursing Home Staffing to Improve Quality

Abstract: Health care providers face fixed reimbursement rates from government sources and need to carefully adjust staffing to achieve the highest quality within a given cost structure. With data from the Certification and Survey Provider Enhanced Reports (1999-2015), this study holistically examined how staffing levels affect two publicly reported measures of quality in the nursing home industry, the number of deficiency citations and the deficiency score. While higher staffing consistently yielded better quality, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
2
48
0
1
Order By: Relevance
“…Adequate staffing levels are required to provide high-quality care to residents. 7,12 A recent article reported that higher RN staffing levels before the pandemic was associated with fewer COVID-19 cases in a sample of Connecticut NHs. 35 A major finding of our study is that staff shortages were associated with COVID-19erelated factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate staffing levels are required to provide high-quality care to residents. 7,12 A recent article reported that higher RN staffing levels before the pandemic was associated with fewer COVID-19 cases in a sample of Connecticut NHs. 35 A major finding of our study is that staff shortages were associated with COVID-19erelated factors.…”
Section: Discussionmentioning
confidence: 99%
“…As of June 15, 2020, CMS published data of the weeks ending on May 24 and 31, 2020 for each certified NH and conducted the quality check of the data. 3 Of the 15,451 NHs with data on May 31, 2020, 80.1% (12,375) passed the quality check. NHs that did not pass the quality check tended to be smaller, for-profit, and with lower five-star ratings.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, according to providers, the mission or location of a facility can lead to lower performance on the QMs, regardless of the quality of care provided. In addition to more risk adjustment, higher Medicaid rates might encourage facilities to accept more Medicaid residents and provide resources to support better care, such as through higher staffing levels (Bowblis & Applebaum, 2017;Bowblis & Roberts, 2018;Harrington et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Results for two of the three bandwidths are not statistically significant, and no visual discontinuity is apparent in total social services staffing. To the extent that total social services staffing increases, this would likely bias findings toward finding quality improvements, as prior work suggests that increased social services staffing improves SNF quality (Bowblis and Roberts 2018). across inputs, reducing capital or other types of labor to offset the increase in QSWs.…”
mentioning
confidence: 99%